Proceedings of the 48th Design Automation Conference 2011
DOI: 10.1145/2024724.2024740
|View full text |Cite
|
Sign up to set email alerts
|

To DFM or not to DFM?

Abstract: Design for manufacturability (DFM) is inevitable because of the formidable challenges encountered in nano-scale integrated circuit (IC) manufacturing. Unfortunately, it is difficult for designers to understand the cost-benefit tradeoff when tuning their design through DFM to achieve better manufacturability. This work attempts to assist the designer in this aspect by providing a methodology (called RADAR ---Rule Assessment of DefectAffected Regions) which uses failing-IC diagnosis results to systematically eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The methodologies developed include evaluating the effectiveness of DFM (design-for-manufacturability) rules [24] in systematic-defect prevention, identifying and understanding systematic defects [25] to guide process improvement effort, formulate new DFM rules [26] or identify targets for test [22,27], and creating a framework for fast and accurate defect simulation [28] to validate these and other emerging test/yield learning methodologies (e.g., [29]). for the three shaded bubbles in Figure 5, which indicate the three problems addressed in this dissertation.…”
Section: This Is Illustrated Inmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodologies developed include evaluating the effectiveness of DFM (design-for-manufacturability) rules [24] in systematic-defect prevention, identifying and understanding systematic defects [25] to guide process improvement effort, formulate new DFM rules [26] or identify targets for test [22,27], and creating a framework for fast and accurate defect simulation [28] to validate these and other emerging test/yield learning methodologies (e.g., [29]). for the three shaded bubbles in Figure 5, which indicate the three problems addressed in this dissertation.…”
Section: This Is Illustrated Inmentioning
confidence: 99%
“…Since X 10 and X 00 appears in the numerator and denominator of the odds ratio expression, respectively, their effect will be cancelled out. It should be noted that a different metric was used in the earlier version of RADAR [63]. When performing validation of RADAR using simulation experiments (to be discussed in detail in Section 2.4.2), it is found that, while the earlier metric gave the correct rule ranking, it cannot be reliably interpreted because it is dependent on the amount of passing data collected and therefore is not invoked here.…”
Section: Relative Risk Estimationmentioning
confidence: 99%
See 3 more Smart Citations